1982
DOI: 10.1007/bf00848417
|View full text |Cite
|
Sign up to set email alerts
|

Developmental profiles of gangliosides in mouse and rat cerebral cortex

Abstract: Developmental profiles of 11 gangliosides, concentration of lipid- and glycoprotein-bound sialic acid, and activity of AChE of the rat and mouse cerebral cortex were followed from the 7 day of gestation to the 21 postnatal day.There are three main changes in ganglioside concentration, which are similar in both species. The first occurs from gestation day 10 until birth: parallel to decreased proliferation, cell migration, and neuroblast differentiation, G and G in mouse cortex and G in the rat's decreases in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
2

Year Published

1983
1983
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 30 publications
3
16
2
Order By: Relevance
“…Yavin and Yavin [11] reported that the increase in sialic acid and the developmental patterns of ganglioside spe cies in cultured rat cerebral cells agree with those in the developing prenatal brain. Similar observations have been made in other neuronal systems [12,13]. Dreyfus et al [10] proposed two discrete periods of changes in gan glioside concentration and pattern using cultured neu rons from 8-day-old chick embryonic brain.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Yavin and Yavin [11] reported that the increase in sialic acid and the developmental patterns of ganglioside spe cies in cultured rat cerebral cells agree with those in the developing prenatal brain. Similar observations have been made in other neuronal systems [12,13]. Dreyfus et al [10] proposed two discrete periods of changes in gan glioside concentration and pattern using cultured neu rons from 8-day-old chick embryonic brain.…”
Section: Discussionsupporting
confidence: 52%
“…In general, the period of synapse formation is marked by a decrease o f GD3 and an increase of G D la. The changes in ganglioside composition such as a decrease o f GD3 and an accretion of more complex gangliosides mimic developmental changes in embryonic rat and mouse brains [11][12][13], In the rat brain the change from synthesis of GM3 and GD3 to that of GM1 and G D la is reported to occur after embryonic day 18 [14].…”
Section: Introductionmentioning
confidence: 99%
“…We also studied the cell responsiveness to triiodothyronine by following its effect on in dexes such as cerebroside sulfotransferase (CST), an enzyme in oligodendroglia which is involved in the production of myelin sulfatides [73,[81][82][83], and gangliosides, which are particularly abundant in neuronal cells [18] and which show variations in their de velopmental pattern during cell maturation [8,29,32,54,55]. Preliminary accounts of these results have been published in abstract form [3,4,22],…”
Section: Introductionmentioning
confidence: 99%
“…Gangliosides are thought to play an im portant role in neuronal development be cause they are heavily concentrated in neu ronal membranes and undergo significant changes during neuronal differentiation and brain development [Ledeen, 1983;Fishman and Brady, 1976;Dreyfus et al, 1980;Irwin, 1979, 1982;Irwin et al, 1980;Landa and Moscona, 1985a, b;Yu et al, 1988;Rosner, 1980Rosner, , 1982Rosner et al, 1985;Yavin and Yavin, 1979;Engel et al, 1979;Hilbig et al, 1982;Seyfried et al, 1983Seyfried et al, , 1984. Before neuronal differentia tion, however, ganglioside composition is similar in neural and nonneural embryonic tissues [Bouvier and Seyfried, 1989].…”
Section: Discussionmentioning
confidence: 99%